Analisis usaha teh herbal daun gambir “Afiyah” pada Kelompok Usaha Bersama (KUBE) Sambal di Nagari Talang Maur Kabupaten Lima Puluh Kota - Afifah, Fayi; Febriamansyah, Rudi; Fitriana, Widya (Universitas Halu Oleo, 2023)
KUBE Sambal as a business institution aims to gain profit in every activity. Therefore, the aim of this research is: to describe the business profile, analyze the feasibility and break-even point of the KUBE Sambal business. The method used is the survey method. Data was taken through observations and interviews which included business profile data, sales results, total costs, selling prices and production volume from April to May 2021. Data was analyzed using Revenue Cost Ratio (R-C Ratio) and Break-Even Point (BEP) analysis. The research results show that the KUBE Sambal business has not developed, where the production, marketing and general administration aspects require many improvements and changes. Apart from that, this business is feasible to run because the R-C Ratio value is 1.34 which is greater than 1. Then, this business is also above the break-even point for product quantity and also break-even sales. Break-even product quantity is 106 units with break-even sales of IDR 1,599,598.-. Keywords: business analysis; R-C ratio; break-even point; gambir leaf herbal tea